Penerapan Sistem Pendukung Keputusan Pemilihan Cleaning Servis Terbaik Menggunakan Kombinasi Metode Pembobotan Entropy dan COPRAS - Nuari, Reflan; Setiawansyah, Setiawansyah; Mesran, Mesran (Building of Informatics, Technology and Science (BITS), 2024)
The main problem in choosing the best cleaning service is often a challenge because it involves a variety of complex and subjective criteria. Cleaning service performance assessments are not only based on factors such as speed and efficiency in work, but also include other aspects such as cleanliness of work results, interpersonal skills, and the ability to comply with safety procedures. The purpose of this research is to implement a system that is able to evaluate and select cleaning service providers objectively and effectively. The Entropy method to measure and assign weights to relevant criteria in the assessment of cleaning service providers, based on the information contribution of each criterion. The COPRAS method to assess and compare various alternative cleaning service providers based on the weight of predetermined criteria, so as to identify the service provider that best meets the desired needs and standards. Based on the results of the ranking that has been carried out by applying the entropy and COPRAS weighting methods, Hadi Santoso occupies the top position with a perfect score of 100, showing that he is the best cleaning service employee among other candidates. Dewi Lestari is ranked second with a score of 96.07, which also shows a very good performance but slightly below Hadi. Meanwhile, Haryani occupies third place with a score of 92.46. Even though it is in last place, this score still reflects a fairly satisfactory performance. This difference in scores indicates a variation in the performance aspects assessed, so that it can be used as a basis for decision-making for awards or service quality improvement.